Association between airway microbiota and systemic inflammation markers in non-small cell lung cancer patients - DanHui Huang; QianNan Ren; LingYan Xie; YueHua Chen; Cui Li; XiaoFang Su; LiShan Lin; LaiYu Liu; Haijin Zhao; Tingyue Luo; JianHua Wu; Shaoxi Cai; et al. (Scientific Reports)
Abstract Growing evidences have suggested the airway microbiota may participate in lung cancer progression. However, little was known about the relationship between airway microbiota and lung cancer associated systemic inflammation. Here we aimed to explore the association between sputum microbiota and systemic inflammation in lung cancer. The microbiota of spontaneous sputum samples from 51 non-small cell lung cancer (NSCLC) patients and 6 patients with lung benign nodules were sequenced via 16 S rRNA sequencing. Neutrophil-lymphocyte ratio (NLR), platelet–lymphocyte ratio (PLR) and C reactive protein (CRP) were used to represent systemic inflammation. Patients were divided into 2 groups based on level of inflammatory biomarkers respectively (CRP_low versus CRP_high; NLR_low versus NLR_high; PLR_low versus PLR_high). α-diversity was significantly decreased in CRP_high and NLR_high patients. β diversity analysis based on weighted unifrac distance indicated that microbial community structure differed significantly between patients with different inflammation status. Lefse identified genera Porphyromonas, Selenomonas, Moryella, Megasphaera, Corynebacterium were enriched in CRP_low group. Compared with NLR_high, genera Veillonella, Neisseria, Bulleidia, Moryella were enriched in NLR_low group. For patients with different PLR level, genera Veillonella, Prevotella, Moryella, Selenomonas were increased in PLR_ low patients. Function analysis identified propionate metabolism pathway was significantly enriched in CRP_low and PLR_low groups. Moreover, RDA analysis showed that compared with PLR, NLR and CRP had strongest association with microbial community. Airway microbial structure differed between lung cancer with different systemic inflammation status. Patients with relative high inflammation status were associated with alteration of specific airway genera and microbial metabolic function.